Kinematika Robot dengan Sistem Kendali Proportional Integral dan Derivative menggunakan Sensor IMU pada Robot Hexapod - Ali Ilham Ainur Rahman; Rizal Maulana; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Indonesian Robot Contest (KRI) 2021 with one of its divisions, the Indonesian Robot Search and Rescue Contest (KRSRI), raised the background on the disaster environment with robots as a solution. There are obstacles on the path of the robot labyrinth as a manifestation of the irregularity of the disaster environment, using the obstacle board. A hexapod robot is a legged robot that can move if a certain movement pattern is applied with mathematical calculations such as inverse and body kinematic. The addition of a body kinematic, instead of inverse kinematics only, allows the robot to not only move sideways, forward and backward, but the addition of rotating motion is also possible. The hexapod robot is very possible to apply gait so that the robot can walk, three of which are tripod, wave, and ripple gait. Even though the robot is designed in such a way, there is still the possibility that there will be an error value during movement due to the imperfection of the system. The solution to reducing this value can be the application of a Proportional, Integral, and Derivative (PID) control system on the system. While the PID gain value can be found using the Zeigler-Nichols method which looks for the sustained oscillation signal from the system. On the yaw axis of the robot, the PID sustain oscillation values ​​are 1,23s, 2,1, for the pitch and roll axes of the robot to maintain balance, the sustain oscillation values ​​are 0,51s, 1,1, while the roll 1,72Hz, 1,2. The results of the robot's walking accuracy after using PID have increased, the tripod step pattern has an MAE (Mean Absolute Error) of 0,62, different from before the PID was implemented at 9,35. Wave and Ripple were previously unable to reach the finish line, with PID robots being able to reach the finish line. The Indonesian Robot Contest (KRI) 2021 with one of its divisions, the Indonesian Robot Search and Rescue Contest (KRSRI), raised the background on the disaster environment with robots as a solution. There are obstacles on the path of the robot labyrinth as a manifestation of the irregularity of the disaster environment, using the obstacle board. A hexapod robot is a legged robot that can move if a certain movement pattern is applied with mathematical calculations such as inverse and body kinematic. The addition of a body kinematic, instead of inverse kinematics only, allows the robot to not only move sideways, forward and backward, but the addition of rotating motion is also possible. The hexapod robot is very possible to apply gait so that the robot can walk, three of which are tripod, wave, and ripple gait. Even though the robot is designed in such a way, there is still the possibility that there will be an error value during movement due to the imperfection of the system. The solution to reducing this value can be the application of a Proportional, Integral, and Derivative (PID) control system on the system. While the PID gain value can be found using the Zeigler-Nichols method which looks for the sustained oscillation signal from the system. On the yaw axis of the robot, the PID sustain oscillation values ​​are 1,23s, 2,1, for the pitch and roll axes of the robot to maintain balance, the sustain oscillation values ​​are 0,51s, 1,1, while the roll 1,72Hz, 1,2. The results of the robot's walking accuracy after using PID have increased, the tripod step pattern has an MAE (Mean Absolute Error) of 0,62, different from before the PID was implemented at 9,35. Wave and Ripple were previously unable to reach the finish line, with PID robots being able to reach the finish line.